Horizontal integration and financial reform of a primary care delivery system in Pengshui County, China: a case study. Issue 1 (October 2019) - Zeng, Zhi; Tao, Wenjuan; Liu, Chunping; Zhou, Lin; Pan, Jianbo; Zhang, Weibin; He, Yu; Zhang, Wei; Zhao, Rui
Abstract: Background: The major obstacles to strengthening the primary care system in China are shortages of finance and workforce, especially in rural and low-income areas. To address these barriers, in 2009, Pengshui County (Chongqing, China), implemented a reform on its primary care delivery system, with a focus on horizontal integration and financing mechanisms. We aimed to analyse the horizontal integrated-care model and evaluate the effect of the reform in the past 10 years. Methods: We analysed the reform to the primary care delivery system in Pengshui County, focusing on the design and implementation of the horizontal integrated-care model, as well as its financial mechanisms. A descriptive, explanatory, evaluative case study was conducted based on analysis of national and local policy documents, in-depth interviews with local policy makers and institution managers in March, 2019, and analysis of pre-reform and post-reform administrative data from provincial and local health administrative departments. Findings: Implementation of the reform was characterised by establishment of a commission of primary care and a policy-coordinating board, which was charged with managing all horizontally integrated primary care providers and strengthening strategic planning and management of Pengshui County's primary care system. Additionally, a primary care funding pool was developed to support facility purchasing, professional development, and financial incentives. The reform was also characterised by performance assessments, with equal emphasis on public health care and basic medical services, and an enhanced compensation system to encourage uptake of grassroots medical posts by the primary care workforce. From 2009 to 2018, the number of primary care health professionals increased by 125% (from 1113 to 2510). The proportion of outpatients who sought first-contact care in rural community health centres or township health centres increased from 29% (522 700 of 1 817 600) in 2009 to 40% (849 900 of 2 147 800) in 2018 (the national average in 2018 was 23%). From 2009 to 2018, the proportion of inpatients in primary medical institutions decreased slightly from 67% (30 528 of 45 450) to 60% (93 273 of 156 166), marking a decline rate that was 6 percentage points lower than the national average (the national average decreased from 31% to 17%). However, numbers of inpatients tripled in the same period. The mean annual payment to primary care staff was ¥120 800 (SD 25 615) in 2018, which was five times higher than in 2009. Interpretation: Our study suggests that a high priority of Pengshui County's reform strategy was the mobilisation of enough resources to finance efficient and equitable provision of primary care. The horizontal integrated-care model established a clear division of responsibilities and governance structure. The policy of fundraising and mutual aid-sharing of compulsory payment improved the financing and compensation mechanism and made up for the problem of insufficient investment. Many positive results have been achieved through the reform, including advanced medical facilities, more qualified medical professionals, better capability of primary health care, and improved patients' trust of public health and primary medical services. Pengshui County's experience represents a successful experiment in the development of integrated-care reform, especially for rural and low-income regions. Funding: World Bank China and Science and Technology Department of Chongqing.